Rivers of Europe - Tockner, Klement; Zarfl, Christiane; Robinson, Christopher T. (Elsevier, 2022)
Rivers of Europe, Second Edition, presents the latest update on the only primary source of complete and comparative baseline data on the biological and hydrological characteristics of more than 180 of the highest profile rivers in Europe. With even more full-color photographs and maps, the book includes conservation information on current patterns of river use and the extent to which human society has exploited and impacted them. Each chapter includes up to 10 featured rivers, with detailed information on their physiography, hydrology, ecology/biodiversity and human impacts. Rivers selected for specific coverage include the largest, the most natural, and those most affected by humans. This book provides the most comprehensive information ecologists and conservation managers need to better assess their management and meet the EU legislative good governance targets.